Metal leaching test of commercially available faucets in the Japanese market in 2016–2020. (29th June 2022) - Miyoshi, Taro; Simazaki, Dai; Tokuyasu, Marina; Masuda, Takanori; Akiba, Michihiro
Abstract: In this study, metal leaching was investigated in commercially available faucets in Japan to clarify their compliance to Japanese regulations. We purchased 37 faucets from the market and analyzed the leaching of cadmium, mercury, selenium, lead (Pb), arsenic, hexavalent chromium, boron, zinc (Zn), copper, manganese, and nickel. The leaching tests were performed with and without a conditioning treatment, that simulated approximately 1-month intermittent use of faucets on weekdays, and the results were compared to estimate the changes in metal leaching during the use of faucets. The results revealed that metal leaching from most of the faucets complied with Japanese regulations. However, the levels of Pb leaching from several faucets produced by certain manufacturers exceeded the Japanese standard. The conditioning treatment was generally effective in reducing metal leaching. However, the reductions in Pb and Zn leaching tended to be lower than those of the other metals. Nickel is not legally regulated in Japan; although the number of cases where nickel concentration in leachate exceeded the water quality management target value was greater, such cases were limited to faucets primarily made of copper alloys. We believe that these results will be helpful to improve the public health associated with metal leaching from faucets. HIGHLIGHTS: Metal leaching was tested in commercially available faucets in Japan. Leaching with and without conditioning was tested to estimate time-course decline in metal leaching. Faucets of a certain manufacturer repeatedly exceeded the Japanese standard. The declines in Pb and Zn leaching by the conditioning were limited. Using faucets not made mainly of copper alloys may be useful to reduce the effect of nickel leaching. Graphical Abstract